New methods applied to interpretations of pollen data in the Holocene - selected examples from the last decade - Pidek, Irena A.; Filbrandt-Czaja, Anna; Noryśkiewicz, Agnieszka; Noryśkiewicz, Bożena; Räsänen, Satu (Ecological Questions, 2009)
The results of palynological analyses of the Holocene deposits and modern pollen deposition in Poland and Finland are used to illustrate the progress in pollen analysis - the main palaeoecological method. The increased potential of modern palaeoecology for reconstruction of vegetation and for drawing conclusions on other environmental variables (climate, water conditions, landscape, anthropogenic disturbances) is demonstrated. Pollen analysis - develops at present interpretive tools for precise reconstruction of the structure and composition of vegetation and climate conditions. The progress consists in the quantitative presentation of pollenvegetation-climate relationships based on the examination of modern pollen deposition. The application of numerical analyses to pollen data allows correlating pollen spectrum features with the landscape/vegetation type. Special attention is paid to the Holocene vegetation changes of the transitional zone between boreal forest and tundra in the areas subjected to weak anthropopression (e.g. Lapland), which reflect climatic changes. Databases of modern pollen analogues are based on analysis of samples of surface mosses and contents of Tauber traps. These traps are used in Poland in investigations conducted as a part of the Pollen Monitoring Programme (http://pmp.oulu.fi). The correlation of Tauber-trap data with aerobiological ones contributes to understanding of the relationship between pollen production and climate elements. Additionally, the precise C 14 dating allows a near-annual resolution in fossil deposits to be obtained more frequently. Due to time scales comprising hundreds of years, pollen analysis can provide means to resolve questions inaccessible for direct observation.